Normas processuais civis simbólicas: um estudo sob a ótica da teoria sistêmica de Niklas Luhmann - Altoé, Fabiano Medani Frizera (2023)
This dissertation aims to analyze the allopoietic phenomenon – derived from the Greek alo (“another”, “different”) and poiesis (“creation”, “production”) – in the construction of civil procedural legal norms, especially those present in Book I, Sole Title, Chapter I, of Law nº 13.105/2015 (Code of Civil Procedure). Such activity allows the entry of symbolic norms into the system of positive law, whose contents are limited to a) the confirmation of the values of one group to the detriment of another, relegating the normative effectiveness of the law to the background; b) the expansion of commitments, with the transfer of the solution to the conflict to an indefinite future, and; c) the strengthening of citizens' confidence in the government (alibi legislation), exposing the State, when legislating, as a figure worthy of trust and that meets social aspirations. Based on the premises of the systemic theory elaborated by Niklas Luhmann, which emphasizes autopoietic, self-referential and operationally closed systems, this work provides the reader with a reflection on the dejuridicizing connotation of allopoietic paradigms that interfere in the systemic identity of law. It does not forget that the law must be constantly adapting to social reality, presenting effective means for conflict resolution. However, it will be shown that the presence of symbolic legislation is often responsible for distorting the legitimate function of civil procedural law and violating its principles. This work, through the use of the inductive method and descriptive bibliographic research, is primarily concerned with positioning the study within the communicational theory of law and the theory of legal norms; in a second moment, in presenting the law as an autopoietic system and the theory developed by Niklas Luhmann; in a third moment, to explain the interference of an allopoietic activity in the legal-systemic context, causing systemic corruption; in a fourth moment, in demonstrating the meaning of a symbolic legislation, as well as its possible consequences when such norms are inserted in the civil procedural diploma, and; finally, to point out the symbolic legislation present in CPC/2015 and answer whether the introduction of these norms implies the formation of an allopoietic activity within the scope of the positive law system.